Analysis of Salt Policy and Its Impact On Farmers: Balancing Regulation And Protection - WINDA, Fara; UTAMI, Dea Putri; MAHARANI, Jesica Puspa (Protection: Journal Of Land And Environmental Law, 2025)
Indonesia has great potential in salt production, especially in Cirebon Regency, West Java, thanks to its vast marine area. However, challenges such as low productivity, poor quality, and limited access to technology and capital hinder the development of the local salt industry. Most salt farmers still rely on traditional methods, which results in an imbalance between domestic market demand and production capacity. This research analyzes the regulation related to salt policy and its impact on the welfare of farmers in Waruduwur Village, Mundu Sub-district, Cirebon Regency, West Java Using a case study-based qualitative approach, this research explores the role of government policy in overcoming capital and technological barriers, such as the application of geomembranes. The results are expected to offer recommendations to achieve a balance between effective regulation and protection of farmers in order to improve their welfare, reduce import dependency, and strengthen the competitiveness of local salt in the national market.